I swear I saw this Drawings in fieldwork notebooks, namely my own - Sempio Durán, Camilo (Alteridades, 2014)
Reseña del libro de Michael Taussig, I swear I saw this. Drawings in fieldwork notebooks, namely my own, The University of Chicago Press, Chicago, 2011, 173 pp.